Probability of brick structures destruction - Kichaeva, Oxana (Academic journal Industrial Machine Building Civil Engineering, 2019)
The results of calculations of construction brick destruction probability determination at central and off-center compression are given; the determination of the brick structures destruction probability, caused by the exhaustion of the masonry strength on local compression (crushing); determination of the brick structures destruction probability associated with the exhaustion of the masonry strength on the displacement (cut); determination of the brick structures destruction probability associated with the exhaustion of the masonry strength on the fold, the stretch; determination of the brick structures destruction probability on the crack opening. The value of the security characteristic for each case has been determined and the comparison with the normative values has been made.